Peningkatan Kompetensi Pemasaran Produk Melalui Pelatihan Digital Marketing Bagi Pelaku UMKM - Ardiyansyah Ardiyansyah; Fahrizal Fahrizal; Ayu Nurkhayati (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2023)
The purpose of this community engagement activity is to provide additional knowledge and skills for business practitioners in the form of Digital Marketing Training, with the aim of boosting product sales for Micro, Small, and Medium Enterprises (MSMEs) in Pamucak Village, Cermin Nan Gedang District, Sarolangun Regency. The implementation method of this engagement activity comprises several stages. First; the preparation and Field Survey Phase, The activity commences with the preparation and field survey phase. During this stage, the team engages in direct discussions with the village authorities and community leaders of Pamuncak Village to identify the needs, opportunities, and challenges faced by MSME business practitioners in the village. Second; the socialization and Training Phase, The team proceeds with the socialization and training phase. The training content is centered around digital marketing strategies. Through this socialization and training, participants are equipped with the necessary knowledge and skills to understand and implement digital marketing strategies. The results of this engagement indicate that participants' knowledge prior to the engagement, for the most part, fell within the category of having a limited understanding of digital marketing. However, following the implementation of the engagement in the form of digital marketing training, a significant improvement has been observed in participants' understanding and knowledge of digital marketing skills. As a result, MSME practitioners can optimize digital marketing as a means to enhance their product sales. Furthermore, it is hoped that MSME practitioners can better confront the challenges of digitalization and utilize online-based marketing opportunities more effectively.